Buddhist Ethical Philosophy in Contemporary Education - - Sumaryati; - Lasiyo (RUDN Journal of Philosophy, 2024)
Buddhist ethics is an interesting teaching of Buddhism, emphasizing the acceptance of suffering ( dukkha ). When individuals acknowledge, identify the causes, and strive to alleviate dukkha , they attain nobility and sanctity. The Buddhist ethics is crucial to be implemented in education, particularly among teachers. In the 21st century, teachers must possess information technology, communication, collaboration, critical thinking, problem-solving, innovation, and numeracy literacy skills. Buddhist ethics provide insights on how to approach these demands wisely for teachers. This research aims to explore the application of Buddhist ethics as an alternative means to enhance teacher’s competence in the 21st century. The study employs a qualitative descriptive research approach, collecting data through a literature review on Buddhism and teacher ethics. Data analysis is conducted using interpretation and hermeneutics. Implementing the Four Noble Truths in contemporary education reveals that teachers positively accept their duties problems ( dukkha ), the problem’s cause from their inability to control material desires, have peace, and carry out tasks according to their abilities and capacities. The implementation of the eight noble paths by teachers is to speak honestly, smoothly, and usefully, carry out duties for social interests, have respect for students and the environment, and not harm others. Teachers cleanse themselves of evil and unhealthy thoughts, sensory lust, resentment, doubt, and greed, explain each learning material objectively, show good faith, friendly and pleasant. Buddhist ethics are universal, requiring elaboration in normative provisions in various fields of life. Thus, Buddhist ethics contributes to the advancement of human civilization.